Pertumbuhan Dan Hasil Padi (Oryza sativa. L) Melalui Aplikasi Zink Sulfat - Maulana, Muhammad Iqbal Hakim; Widodo, Tirto Wahyu; Jumiatun, Jumiatun; Soelaksini, Liliek Dwi (Agropross : National Conference Proceedings of Agriculture, 2023)
East Java rice production in 2021 reach 9.79 million tons.ha-1, but it decrease to 9.69 million tons.ha-1 in 2022. One effort to increase rice production can be done by adding zinc sulfate. Zinc plays a role in increasing the photosynthetic metabolism of plants, thereby it’s triggering growth and yield of rice. This study aims to examine the effect of the addition and time of application of zinc sulfate on rice growth and yield. The experiment was designed using a factorial Completely Randomized Design (CRD) consisting of 2 factors and 4 replications. The first factor was the dose of zinc sulfate which consisted of 4 levels: 0, 8, 12, and 16 kg.ha-1. The second factor was the application time, namely 10 dap and 40 dap. The results showed that there was no interaction between zinc sulfate dosage and application time on rice growth and yield. The application of zinc sulfate 16 kg.ha-1 showed significant results on plant height (144.83 cm), number of tillers (28.33 tillers), number of hot grain per panicle (122.58 grains) and weight of grain per clump (47.13 g ). The addition of a zinc sulfate dose of 16 kg.ha-1 was able to increase plant photosynthetic activity and assist in the process of preparing protein so that it affected rice growth and production. While the application of zinc sulfate at the age of 40 dap showed a significant effect on the number of grain per panicle (121.95 grains). This is because the addition of zinc sulfate in the flowering phase can reduce the risk of increased formation of abscisic acid which can cause loss of flower buds and abnormal growth of anthers and pollen grains.